Migration Processes and Identity of the EU - R. Alonzi (Контуры глобальных трансформаций: политика, экономика, право, 2020)
The article delves into the influence of the migration phenomenon on the complex process of the European political Identity-building process. The main research question is: why do migration processes erode the identity of the European Union? Or: what type of European identity is the result of these migratory processes?Firstly, the author defines the difference between European identity and identity of European Union. The character of the latter, being the result of a negotiation process between its members on the shared values to be adopted and the meanings that the Union must assume for its citizens, can be only political. The approaches suggested, sometimes even indirectly, by studies conducted on the matter allow us to deduce that the dynamics of migration processes negatively affect the creation of the political identity of the European Union. Instead, they reinforce its apolitical character. On the one hand, there is not a shared vision between the EU Member States of rules and frameworks to manage migration phenomenon. While there is no agreement between the EU Member States on how to manage migration, the integration policies adopted by the various States are being transformed into policies of disintegration of national identities, without any advantage for the evolution of supranationality. Multiculturalism and pluralism, cosmopolitan citizenship, are variables that run counter to the basic principles of the legitimacy of European power, namely European citizenship, European cultural universalism, the idea of the collective and the particular identity of Europeans.The author concludes that it is, therefore, “metapolitical” values, rather than the structure of the Union itself, that undermines the foundations of European political identity. It is in this context that the disidentitary potential of migratory phenomena finds the conditions for its full accomplishment. It is no coincidence that the metapolitical value that current liberal thought cannot do without is “politically correct”. The “political correctness” is a privileged dimension, which helps European elites interpret the problem of migration in a political sense, and this is reflected in the monolithic nature of the applied narrative, with which they interpret the phenomenon of migration.